Кінетика процесу окиснювального амонолізу ізобутилового спирту на Fe-Te0,85-Mo-(BaCl₂)0,1 оксидному каталізаторі - Мацьків, Олена Олександрівна; Небесний, Роман Володимирович; Івасів, Володимир Васильович; Солодяк, Лілія Йосифівна (НТУ "ХПІ", 2017)
Вивчено кінетичні закономірності реакції окиснювального амонолізу ізобутилового спирту до метакрилонітрилу на Fe-Te0,85-Mo-(BaCl₂)0,1 оксидному каталізаторі. Розраховані константи швидкостей, енергії активації та теплоти адсорбції реакцій утворення продуктів окиснювального амонолізу ізобутилового спирту на Fe-Te-Mo-Ох каталізаторі, промотованому BaCl₂, з оптимальним за виходом метакрилонітрилу співвідношенням Ва/Мо = 0,1 та запропоновано кінетичну модель, яка задовільно описує окиснювальний амоноліз ізобутилового спирту до метакрилонітрилу.

The kinetic regularities of the ammoxidation of isobutyl alcohol to methacrylonitrile on Fe-Te0,85-Mo-(BaCl₂)0,1 oxide catalyst were studied. The effect of temperature and concentrations of the initial reagents (isobutyl alcohol and NH₃) on the formation rate of the reaction products (methacroleine, methacrylonitrile and CO₂) and the conversion rate of the reagents was established. It is shown that with the increase of temperature and concentration of isobutyl alcohol conversion rate of the alcohol and formation rate of the reaction products increases. The established dependence of formation rate of the products of the isobutyl alcohol ammoxidation on the concentration of NH₃ shows that the formation rate of methacrylonitrile is proportional to the concentration of NH₃, and with the increase of NH₃ concentration, the formation rate of methacroleine is greatly reduced. The formation rate of CO₂ at lower temperatures is practically independent of the concentration of NH₃. The orders of the reactions of products formation with respect to isobutyl alcohol and NH₃ are determined. Kinetic equations for the process are derived based on Mars–van Krevelen mechanism. Rate constants, activation energy and heat of adsorption were calculated by linearization of the kinetic equations using obtained experimental data on the reactions of formation of the products of the ammoxidation of isobutyl alcohol on Fe-Te-Mo-Ox catalyst, promoted by BaCl₂, with optimum by methacrylonitrile yield ratio Ba/Mo = 0.1. A kinetic model is proposed that satisfactorily describes the ammoxidation of the isobutyl alcohol to methacrylonitrile and therefore can be used for the technological calculations of the process design.
Kinetic of the ammoxidation process of isobutyl alcohol on Fe-Te0,85-Mo-(BaCl₂)0,1 oxide catalyst
Keywords: метакролеїн; метакрилонітрил; модель кінетична; methacroleine; methacrylonitrile; kinetic model